A targeted immunomic approach identifies diagnostic antigens in the human pathogen Babesia microti. Issue 8 (17th May 2016) - Cornillot, Emmanuel; Dassouli, Amina; Pachikara, Niseema; Lawres, Lauren; Renard, Isaline; Francois, Celia; Randazzo, Sylvie; Brès, Virginie; Garg, Aprajita; Brancato, Janna; Pazzi, Joseph E.; Pablo, Jozelyn; et al.
Abstract : BACKGROUND: Babesia microti is a protozoan parasite responsible for the majority of reported cases of human babesiosis and a major risk to the blood supply. Laboratory screening of blood donors may help prevent transfusion‐transmitted babesiosis but there is no Food and Drug Administration–approved screening method yet available. Development of a sensitive, specific, and highly automated B. microti antibody assay for diagnosis of acute babesiosis and blood screening could have an important impact on decreasing the health burden of B. microti infection. STUDY DESIGN AND METHODS: Herein, we take advantage of recent advances in B. microti genomic analyses, field surveys of the reservoir host, and human studies in endemic areas to apply a targeted immunomic approach to the discovery of B. microti antigens that serve as signatures of active or past babesiosis infections. Of 19 glycosylphosphatidylinositol (GPI)‐anchored protein candidates (BmGPI1‐19) identified in the B. microti proteome, 17 were successfully expressed, printed on a microarray chip, and used to screen sera from uninfected and B. microti –infected mice and humans to determine immune responses that are associated with active and past infection. RESULTS: Antibody responses to various B. microti BmGPI antigens were detected and BmGPI12 was identified as the best biomarker of infection that provided high sensitivity and specificity when used in a microarray antibody assay. CONCLUSION: BmGPI12 alone or in combination with other BmGPI proteins is a promising candidate biomarker for detection of B. microti antibodies that might be useful in blood screening to prevent transfusion‐transmitted babesiosis.